Integral assessment of the level of preparedness of kissboxers based on the harrington-mencher function - Kolyada, M.G.; Belykh, S.I.; Bugaeva, T.I.; Oleinik, O.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the mechanism for identifying a generalized assessment of the level of preparedness of kickboxers. Methods and structure of the study. The application of the Harrington-Mencher desirability function to determine the level of preparedness of kickboxers is presented. The work of the desirability function is that it converts dimensional indicators into dimensionless ones, in fact, generalizes diverse indicators, bringing them to a single complex indicator. Results and conclusions. The technique of an integral assessment of the level of preparedness of a kickboxer using the Harrington-Mencher function is given. A specific example shows the mechanism for converting actual indicators into a 10-point scale, and then into desirability coefficients. Thanks to a special system for translating desirability indicators into the usual rating scale, it is possible to obtain a complex indicator at the output that objectively evaluates their total set. Weight indicators of the significance of the preparedness of kickboxers were determined on the basis of expert assessments, which included reputable kickboxing coaches and referees.